HUKUM BERWASIAT KEPADA NON MUSLIM : DITINJAU DARI PERSPEKTIF HUKUM ISLAM - Rasyid, Arbanur (IAIN Padangsidimpuan, 2020)
This article describes the statute of wills to non-Muslims, which is the main formula in this paper is about how the legal status of wills to non-Muslims, especially regarding wills related to property, so to answer this problem here the author uses a qualitative method, namely seeking from books that discuss this topic, which the author then concludes with the deductive method.In this paper, the author finds that in determining the will to non-Muslims there are disputes among the ulama of the mazhab, some of which are of the opinion that it is haram and some are of the opinion that it is permissible. Even in Indonesia, there is a concept, namely wills, which is an alternative for judges to distribute inheritance to adopted children. Not only that, many experts also interpret the concept of the mandatory will to give to close relatives who do not get an inheritance even though they are in great need of it materially, this is the solution to cover the problem even though the close relative is non-Muslim, as long as the non-Muslim is not an infidel harb namely infidels who fight against Islam.This study is very interesting to study, considering the plurality of Indonesian citizens who of course there is brotherhood between Muslims and non-Muslims, including the rise of interfaith marriages, this study must be developed as their reference in addressing this kind of problem.